THE IMPLEMENTATION OF HYBRID LEARNING POLICY DURING COVID 19 IN MALANG CITY - Taufiq Akbar Al Fajri; Trisna Andarwulan (Universitas Brawijaya, 2022)
Due to the emergence of this virus in the field of education and causing problems in the education system in Indonesia, the Minister of Education and Culture issued regulation No. 4 of 2020 concerning the implementation of Education Policies in the Emergency Period for the Spread of Corona Virus Diseases-19. The policy is asked school to implement hybrid learning, where some of the class is conducted online. This research is conducted to find out the implementation of hybrid learning policy during covid 19 in Malang city. The research method used in this study is qualitative research method. This policy was created to provide guidance to the community in carrying out educational activities. The research conducted through three implementation policy; organization, implementation and application. It is found out that education is a very important thing for the progress of a country. Even during the Covid-19 pandemic, education is required to continue even under emergency conditions. The implementation of hybrid learning policy in schools in Malang city is running effectively. However, there are several problems that can be found such as teacher that prefer to do face to face meeting and some teachers who did not familiar with technology such as zoom.